The evaluation of tibial nerve using shear-wave elastography and ultrasound in patients with systemic sclerosis: A cross-sectional study - Serdar Kaymaz,; Murat Yiğit,; Furkan Ufuk,; Burak Sarılar,; Uğur Karasu,; Veli Çobankara,; Nuran Sabir,; Hakan Alkan, (Archives of Rheumatology, 2023)
Objectives: The study aimed to evaluate stiffness and the cross-sectional area (CSA) of the tibial nerve (TN) using shear wave elastography (SWE) and ultrasound (US) and investigate the relationship of these with disease activity, quality of life, and severity of neuropathic pain in patients with systemic sclerosis (SSc). Patients and methods: This cross-sectional study included 28 SSc patients (1 male, 27 females; mean age: 50±11 years; range, 28 to 67 years) and 22 age- and sex-matched healthy controls (4 males, 18 females; mean age: 48±6 years; range, 37 to 66 years) between March and April 2022. US and SWE were performed on the TN, and CSA and nerve stiffness were measured. The TN was examined by a radiologist, 4 cm proximal to the medial malleolus. A few days later, an evaluation was performed in the second session by a second observer to investigate inter-and intraobserver agreement. Interobserver agreement was evaluated using the intraclass correlation coefficient (ICC). The Scleroderma Health Assessment Questionnaire, European League Against Rheumatism European Scleroderma Trial and Research (EUSTAR) group activity index, and Douleur-Neuropathique 4 scores of the patients were evaluated. Correlations between the questionnaires and measurements of nerve stiffness and CSA were assessed. Results: Patients with SSc had significantly higher stiffness and CSA values of the right TN compared to healthy controls (p<0.001 and p=0.015, respectively). The nerve stiffness values of the right TN were positively correlated with the EUSTAR activity index (p=0.004, r=0.552). The CSA of the left TN was larger in patients with SSc (21.3±4.9 mm2 ) than in controls (12.8±3.4 mm2 ), and the nerve elasticity was positively correlated with the EUSTAR activity index (p=0.001, r=0.618). The interobserver agreement was moderate to good for measuring stiffness and CSA of the TN (ICC were 0.660 and 0.818, respectively). There was a good to excellent intraobserver agreement for measuring stiffness and CSA of TN (ICC were 0.843 and 0.940, respectively). Conclusion: The increased disease activity in patients with SSc is associated with TN involvement, which can be demonstrated by US and SWE.